THE ROLE OF INTANGIBLE VARIABLES AS DETERMINANTS OF TOURIST DECISIONS AND SATISFACTION IN THE SUSTAINABILITY OF SUBAK JATILUWIH AGROTOURISM - Ni Made Classia Sukendar; I Gusti Agung Ayu Ambarawati; I Ketut Adi Mayastika; Desak Gede Fitira Patricia; I Ketut Surya Diarta; Trisha Susana Andrea (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2026)
Subak Jatiluwih Agrotourism, located in Tabanan Regency, is based on the traditional subak system. Maintaining the balance between tourism and subak farming activities is crucial. The role of intangible variables on visiting decisions and satisfaction levels at Subak Jatiluwih has a very important influence. This study aims to analyze the direct influence of trust, image, and service variables on tourist decisions and satisfaction, as well as to analyze the influence of these variables on tourist decisions in mediating tourist satisfaction at Subak Jatiluwih Agrotourism. Sampling techniques with purposive sampling and convenience sampling techniques were used in this study, and based on the calculation of the Slovin formula, the research sample required is 100 respondents from a population of 316.703 visitors. SEM-PLS analysis using SMARTPLS 3.29. The results indicate that tourist trust positively influences both visit decisions and tourist satisfaction. The image variable has a positive effect on visit decisions, while image, service quality, and visit decisions positively affect tourist satisfaction. Furthermore, visit decisions play a significant mediating role in the relationship between trust, agrotourism image, and service quality on tourist satisfaction.